PERAN PEDAGANG DALAM PENYEBARAN ISLAM DI INDONESIA - Sarry, Delly Oktavia Permata; Putra, Deko Rio (Sindoro: Cendikia Pendidikan, 2024)
The spread of Islam in Indonesia was a complex process and involved various actors, one of which was traders. The role of traders was very significant in spreading Islamic teachings to the archipelago, especially through maritime trade routes that connected Indonesia with the Arab world, India and China. Trade relations between regions create intense cultural, economic and religious interactions, allowing for the exchange of Islamic ideas and practices. Muslim traders, both from the Middle East, India and China, played an important role as agents for spreading Islam by adapting and mingling with local society. They established mosques, madrassas, and Muslim communities in trading centers, which laid the foundation for the gradual, peaceful spread of Islam. This study aims to trace the history of the role of traders in the Islamization process in Indonesia and analyze its implications for social, cultural and economic development in this region. Through historical methods, it was found that the contribution of traders in the spread of Islam not only had an impact on religious aspects, but also had a long-term influence on the formation of the social and cultural identity of Indonesian society. Penyebaran Islam di Indonesia merupakan proses yang kompleks dan melibatkan berbagai aktor, salah satunya adalah para pedagang. Peran pedagang sangat signifikan dalam menyebarluaskan ajaran Islam ke Nusantara, khususnya melalui jalur perdagangan maritim yang menghubungkan Indonesia dengan dunia Arab, India, dan Tiongkok. Hubungan perdagangan antarwilayah menciptakan interaksi budaya, ekonomi, dan keagamaan yang intens, sehingga memungkinkan terjadinya pertukaran ide dan praktik Islam. Pedagang Muslim, baik dari Timur Tengah, India, maupun Tiongkok, memainkan peran penting sebagai agen penyebar agama Islam dengan cara beradaptasi dan berbaur dengan masyarakat lokal. Mereka mendirikan masjid, madrasah, dan komunitas Muslim di pusat-pusat perdagangan, yang menjadi fondasi bagi penyebaran Islam secara damai dan bertahap. Studi ini bertujuan untuk menelusuri sejarah peran pedagang dalam proses islamisasi di Indonesia. Melalui metode historis, ditemukan bahwa kontribusi pedagang dalam penyebaran Islam tidak hanya berdampak pada aspek religius, tetapi juga memberikan pengaruh jangka panjang dalam pembentukan identitas sosial dan budaya masyarakat Indonesia.